2020
DOI: 10.18295/squmj.2020.20.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine in the Era of COVID-19 and Beyond

Abstract: NONE

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…This exceptional development in ICT is an outcome of the Digital Oman Strategy, which has among its objectives the elimination of digital literacy and empowering all members of the society to communicate and interact electronically [75]. In fact, we have started witnessing the cultural acceptance of this transformation in healthcare delivery and the demand to sustain it [10,11]. In 2021, a survey to assess the accessibility and use of information technology and telecommunication showed that the percentage of those who owned smartphones and internet access was almost equal (around 94%) among respondents from different governorates in Oman [76].…”
Section: The Cultural and Environmental Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…This exceptional development in ICT is an outcome of the Digital Oman Strategy, which has among its objectives the elimination of digital literacy and empowering all members of the society to communicate and interact electronically [75]. In fact, we have started witnessing the cultural acceptance of this transformation in healthcare delivery and the demand to sustain it [10,11]. In 2021, a survey to assess the accessibility and use of information technology and telecommunication showed that the percentage of those who owned smartphones and internet access was almost equal (around 94%) among respondents from different governorates in Oman [76].…”
Section: The Cultural and Environmental Challengesmentioning
confidence: 99%
“…In many countries, the implementation of restrictive measures that reduced people's social and physical contact and limited their transportation within and between cities to overcome the spread of Coronavirus Disease 19 (COVID-19) was the provoking event that led to the wide adoption of telemedicine as a structured healthcare service [6][7][8]. The situation in the Sultanate of Oman was not different [9][10][11][12]. Despite the growing impetus to widely integrate telemedicine in primary healthcare (PHC) facilities, this service -in its various forms -may not be used by all healthcare providers.…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic has brought about numerous challenges across various sectors, including the healthcare system. Among the affected fields, the provision of healthcare services has been significantly burdened, necessitating the implementation of tools to ensure continuity and deliver high-quality care to patients despite limitations 1. One area greatly impacted is outpatient services, which have experienced a substantial reduction in face-to-face appointments due to physical distancing measures implemented to curb the spread of the pandemic 1.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of telemedicine use during the COVID-19 pandemic include the national-level state health department teleconsultation service initiative, e-sanjeevani, in India [ 3 ], and the locally deployed TELEA telemedicine tool in the Spanish region of Lugo [ 13 ]. Similar tools were used in Saudi Arabia, Taiwan and various countries around the world [ 2 , 17 , 18 ]. Indeed, in a survey of physicians in the Veterans Affairs health-care system in the USA, the majority had not used telemedicine before the pandemic [ 19 ].…”
Section: Introductionmentioning
confidence: 99%